Blago soft winter wheat variety as a national heritage in breeding - П. М. Василюк; Р. А. Вожегова; А. П. Орлюк; Г. Г. Базалій; Л. О. Усик (Plant Varieties Studying and Protection)
In 2011, Blago soft winter wheat variety state examination was completed so that the variety was listed in the National Register of Plant Varieties of Ukraine. Recommended area of dissemination included Steppe, Forest-Steppe and Woodlands. The Blago variety has been developed in the Institute of Irrigated Agriculture at the NAAS of Ukraine and is suitable for cultivation under the conditions of irrigated farming and regular (nonirrigated) farming. This is the only research institution in Ukraine that develops winter wheat varieties for irrigated farming following specific program. As is generally known there are specific conditions at irritated plots. Increased moisture of soil and air, root nutrition mode sufficiently balanced with the elements required constitute special microclimate for the agrocenosis of winter wheat at irrigated soil, which ensure sustainable and high yields across space and time. Nevertheless, not only these conditions facilitate the varieties of wheat, but pests and pathogens as well, thereby maliciousness of the latter, especially that of the diseases, significantly increase compared to nonirrigated crops. The yield potential for Blago as a new variety of winter wheat makes 9 to 10 tons per hectare, and is implemented at irritated lands of the South, as well as in the Woodland and Forest-Steppe of Ukraine. The variety represents a comprehensive use genotype as its high adaptability enables it to be applied as at irrigated, so at nonirrigated lands. The variety is well-balanced in terms of its value for cultivation and use traits.